Innovative Tuition Fee Policies as a Catalyst for Human Resource Development: A Case Study of Sriwijaya University - Novita, Arie; Sobri, Kgs. M.; Putra, Raniasa (Journal Public Policy, 2024)
This study investigates the implementation of tuition fee distribution policies at Sriwijaya University, aimed at enhancing human resource development among lecturers and educational staff. Employing the Grindle policy implementation model-which includes policy content, implementation context, and policy outcomes-this qualitative research identifies key challenges and proposes actionable solutions. The findings highlight several obstacles in the policy's implementation, such as unclear communication regarding scholarship opportunities for lecturers and staff, inconsistencies in the annual disbursement of funds, and delays caused by administrative inefficiencies. Additionally, rigid bureaucratic policies and a multi-level hierarchical structure hinder effective scholarship management. To address these challenges, the study emphasizes the necessity of digital transformation, proposing the adoption of a digital platform to improve information dissemination and streamline administrative processes. Standardizing scholarship disbursement procedures and simplifying bureaucratic workflows are recommended to ensure timely and efficient policy implementation. Moreover, capacity building through staff training and regular monitoring and evaluation mechanisms is crucial for sustaining improvements and aligning the policy with the university’s human resource development goals. These recommendations aim to optimize the policy's impact, fostering a more transparent, efficient, and supportive environment for academic staff development.